1995
DOI: 10.1080/03610739508254275
|View full text |Cite
|
Sign up to set email alerts
|

Age and the Ability To Inhibit Distractor Information in Visual Selective Attention

Abstract: Adult age differences in the effects of different types of distractor interference on visual search were examined. Young adults (mean age = 18.5 years) and older adults (mean age = 69.5 years) performed a target-counting task that required a complete search of a visual display in each trial. Varying numbers of targets were presented alone in displays or were interspersed among eight distractor items that were either categorically related (letters) or conceptually related (numbers representing either the correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 30 publications
(27 reference statements)
3
21
1
Order By: Relevance
“…While many visual functions decline with increasing age, there is converging evidence showing that the speed of visual enumeration, both subitizing and counting (reaction/processing time per visual item) remains largely unchanged with advancing age [15][23], although a few of these studies reported mixed results, suggesting that subitizing range [20], subitizing speed [15], [17], [18] and counting speed [16] might deteriorate slightly. It is important to note that all these studies have focused on reaction time - i.e.…”
Section: Introductionmentioning
confidence: 99%
“…While many visual functions decline with increasing age, there is converging evidence showing that the speed of visual enumeration, both subitizing and counting (reaction/processing time per visual item) remains largely unchanged with advancing age [15][23], although a few of these studies reported mixed results, suggesting that subitizing range [20], subitizing speed [15], [17], [18] and counting speed [16] might deteriorate slightly. It is important to note that all these studies have focused on reaction time - i.e.…”
Section: Introductionmentioning
confidence: 99%
“…4 Older adults are less able to ignore environmental distractors than are young adults, as demonstrate d by age diVerences on simple visual attention tasks as well as more complex tasks such as reading and problemsolving in the face of distraction. For example, the presence of distractors in a visual display disrupts older adults' ability to nd a target item more than it disrupts young adults' ability (e.g., Cremer & Zeef, 1987;Lepage, Stuss, & Richer, 1999;Rabbitt, 1965; but see Kotary & Hoyer, 1995). As the number of distractors increases, so do age diVerences in errors and speed, unless the distractors are easily distinguished from the target or unless they occur in predictable locations (Scialfa, Esau, & JoVe, 1998;Zeef, Sonke, Kok, Buiten, & Kenemans, 1996;see Madden & Plude, 1993 for a discussion of sparing factors).…”
Section: Irrelevant Information From the Environment: The Impact Of Dmentioning
confidence: 99%
“…Several recent studies have examined adult age differences in the speed of subitizing and counting, with mixed results (Kotary & Hoyer, 1995;Nebes, Brady, & Reynolds, 1992;Sliwinski, 1997;Trick, Enns, & Brodeur, 1996). Sliwinski found that speed of subitizing decreased linearly across 20-to 80-year-old adults but that speed of counting did not differ across this age range.…”
Section: Enumerationmentioning
confidence: 99%